2013
DOI: 10.1111/bju.12284
|View full text |Cite
|
Sign up to set email alerts
|

Does robot‐assisted laparoscopic ileocystoplasty (RALI) reduce peritoneal adhesions compared with open surgery?

Abstract: Objectives• To compare perioperative outcomes between open ileocystoplasty and robot-assisted laparoscopic ileocystoplasty (RALI) in a porcine model, as objective data comparing outcomes between these two approaches in children with neurogenic bladder are lacking.• We specifically examined differences in postoperative peritoneal adhesion formation between the groups. Materials and Methods• In all, 20 pigs were assigned to an open ileocystoplasty or RALI study arm. All the pigs underwent an initial urodynamic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Following the first case report of RAI by Gundeti et al [95] in 2008, 64 cases have subsequently been reported in the literature in 13 publications. Seven of these were single case reports and of the remaining six articles, five were published from the same group encompassing similar time periods [96] , [97] , [98] , [99] , [100] , [101] .…”
Section: Robot-assisted Augmentation Ileocystoplasty (Rai)mentioning
confidence: 99%
“…Following the first case report of RAI by Gundeti et al [95] in 2008, 64 cases have subsequently been reported in the literature in 13 publications. Seven of these were single case reports and of the remaining six articles, five were published from the same group encompassing similar time periods [96] , [97] , [98] , [99] , [100] , [101] .…”
Section: Robot-assisted Augmentation Ileocystoplasty (Rai)mentioning
confidence: 99%
“…Laparoscopic surgery, however, can significantly reduce adhesions and therefore make repeated resections more viable. [1718] LRLR has been widely used in the treatment of HCC due to the advantages of being minimally invasive, but LRLR is still not the typical procedure used for rHCC. If it can be proved that LRLR has similar validity and safety as ORLR, then it may become more widely used.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we have shown in a porcine model that there are decreased numbers and complexity of adhesions with robotic ileocystoplasty over a conventional open approach. [30] Given that many spina bifida patients require multiple abdominal surgeries over the course of their lives, decreased adhesions may result in decreased complications in the long run. There may be many more benefits that have yet to be quantified or manifested given the relatively short time course of robotic surgery to date.…”
Section: Procedural Applications and Outcomesmentioning
confidence: 99%